A importância da arte em uma educação emancipadora (Olhares, 2019)
Positive argumentation about the importance of the art like emancipation skill and fundamental object at the educational process. Speaks about development of sensibility and its important rule for subjectivity`s enhancement, and its range of action on the social life. Starting at the educational prospects by Ana Mae Barbosa, Jacques Rancière and Paulo Freire, and the Karl Marx’s ontological conception, develop a debate about the value of the art on the knowledge acquirement process and individual emancipation, deepening arguments about emancipatory power of artistic activity on pedagogic process.
Keywords: Art on education; Emancipatory education; Sensibility development; Creativity